Evaluation of the association between climate warming and the spread and proliferation of Ixodes scapularis in northern states in the Eastern United States - Rebecca J. Eisen; Lars Eisen (Ticks and Tick-Borne Diseases, 2024)
Ixodes scapularis (the blacklegged tick) is widely distributed in forested areas across the eastern United States. The public health impact of I. scapularis is greatest in the north, where nymphal stage ticks commonly bite humans and serve as primary vectors for multiple human pathogens. There were dramatic increases in the tick's distribution and abundance over the last half-century in the northern part of the eastern US, and climate warming is commonly mentioned as a primary driver for these changes. In this review, we summarize the evidence for the observed spread and proliferation of I. scapularis being driven by climate warming. Although laboratory and small-scale field studies have provided insights into how temperature and humidity impact survival and reproduction of I. scapularis, using these associations to predict broad-scale distribution and abundance patterns is more challenging. Numerous efforts have been undertaken to model the distribution and abundance of I. scapularis at state, regional, and global scales based on climate and landscape variables, but outcomes have been ambiguous. Across the models, the functional relationships between seasonal or annual measures of heat, cold, precipitation, or humidity and tick presence or abundance were inconsistent. The contribution of climate relative to landscape variables was poorly defined. Over the last half-century, climate warming occurred in parallel with spread and population increase of the white-tailed deer, the most important reproductive host for I. scapularis adults, in the northern part of the eastern US. There is strong evidence for white-tailed deer playing a key role to facilitate spread and proliferation of I. scapularis in the US over the last century. However, due to a lack of spatially and temporally congruent data, climate, landscape, and host variables are rarely included in the same models, thus limiting the ability to evaluate their relative contributions or interactions in defining the geographic range and abundance patterns of ticks. We conclude that the role of climate change as a key driver for geographic expansion and population increase of I. scapularis in the northern part of the eastern US over the last half-century remains uncertain.